Microbiological profile and antimicrobial resistance among diabetic foot infections in Lebanon. Issue 6 (11th August 2020) - Jouhar, Lamia; Jaafar, Rola F.; Nasreddine, Rakan; Itani, Omar; Haddad, Fady; Rizk, Nisrine; Hoballah, Jamal J.
Abstract: Diabetic Foot Infection (DFI) is a challenging complication of diabetes mellitus with a high burden in the Middle East where there is a marked increase in diabetes prevalence and complications. Early detection of DFI and the infectious organisms could result in the early initiation of appropriate antibiotic therapy and improved outcomes. DFI microbiological profiles differ between countries. In our region, Western guidelines are used when initiating treatment for DFI in the absence of local guidance. The purpose of our study was to determine the microbiologic profile and antimicrobial susceptibility of the DFI admissions at a large tertiary referral centre in Beirut and review other reported series in Lebanon and our region. This is a retrospective observational study of patients with DFI admitted to the American University of Beirut Medical Centre from January 2008 to June 2017. The bacteriologic isolation and antimicrobial susceptibility tests were performed according to standard microbiological methods. Between 2008 and 2017, 319 diabetic patients with DFU were admitted to AUBMC, and deep‐tissue cultures were taken for 179 patients. From 179 deep tissue cultures, 314 bacterial isolates were obtained. Fifty‐four percent of patients had the polymicrobial infection. Aerobic gram‐negative rods (GNR) were more prevalent than gram‐positive cocci (GPC) (55%, 39%, respectively). The most common isolate was Escherichia coli (15%) followed by Enterococcus (14%) and Pseudomonas aeruginosa (11%). Staphylococcus aureus isolates accounted for 9% with 50% of them being methicillin‐resistant (MRSA). Among Enterobacteriaceae, 37% of isolates were fluoroquinolone‐resistant, 25% were ESBL producers, and 2% were carbapenem‐resistant. Antibiotic resistance was significantly associated with prior usage of antibiotics. Anaerobes were isolated in 1% and Candida species in 5% of isolates. The sensitivity, specificity, PPV, and NPV of swab culture recovery of pathogens compared with deep tissue culture were (76%, 72%, 76%, 72%) and (94%, 81%, 91%, 86%) for gram‐positive and gram‐negative organisms, respectively. The microbiological profile of DFI in Lebanon is comparable to other countries in the MENA region with big differences compared with the West. Therefore, it is imperative to develop local guidelines for antimicrobial treatment. The high prevalence of GNR in DFI and the high fluoroquinolone resistance should be taken into consideration when choosing empiric antibiotics. Empiric treatment for MRSA or Pseudomonas does not appear necessary except for patients with specific risk factors.